Nutrition and Quality of Life for Patients with Chronic Disease (MDPI - Multidisciplinary Digital Publishing Institute, 2026)
This Special Issue focuses on the impact of nutrition on the quality of life of patients with chronic diseases, including heart disease, kidney disease, diabetes, hypertension, cancer-related malnutrition, and digestive disorders. It brings together research on dietary interventions, nutrient deficiencies, and lifestyle factors that affect health outcomes. By addressing both clinical and psychosocial dimensions of chronic illness, this reprint offers practical, evidence-based insights to support patient care and promote well-being through nutrition-focused strategies.